2007
DOI: 10.1007/s11747-006-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Consumer online privacy concerns and responses: a power–responsibility equilibrium perspective

Abstract: We use the Power-Responsibility Equilibrium (PRE) framework and advance that consumers balance perceived deficits in privacy protection by power holders (businesses and regulators) with defensive actions. In our model, consumer privacy concern is the endogenous mediating entity linking business policy and regulatory perceptions to negative online user responses. The model was empirically tested and confirmed in an experimental setting. In a second study, we added the nature of consumer information involved int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
244
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(257 citation statements)
references
References 27 publications
5
244
0
8
Order By: Relevance
“…For example, if smartphone users perceive that mobile marketers are acting responsibly and thus respecting privacy policies and that sufficient legal regulations are in vigor and in practice, then these users are expected to show less concern for potential privacy violation, and therefore not resort to balancing operations. But if those in power positions are not perceived as acting responsibly, consumer concern is likely to intensify, leading to defensive measures [27]. These responses are consistent with utility maximization theory in that consumers will make specific trade-offs in the online setting to minimize foreseeable losses (e.g., [38]).…”
Section: Defensive Responsesmentioning
confidence: 53%
See 2 more Smart Citations
“…For example, if smartphone users perceive that mobile marketers are acting responsibly and thus respecting privacy policies and that sufficient legal regulations are in vigor and in practice, then these users are expected to show less concern for potential privacy violation, and therefore not resort to balancing operations. But if those in power positions are not perceived as acting responsibly, consumer concern is likely to intensify, leading to defensive measures [27]. These responses are consistent with utility maximization theory in that consumers will make specific trade-offs in the online setting to minimize foreseeable losses (e.g., [38]).…”
Section: Defensive Responsesmentioning
confidence: 53%
“…Lwin et al [27] found that informationprivacyconcernsinluencecustomers'apprehensionanduneasiness over the use of their personal data, which ultimately controls their resultant defensive responses. In the light of utility maximization theory, information privacy in m-commerce has become a prominent concern because ubiquitous multimedia capacity enables firms to collect significant amounts of personal information and to store it indefinitely for later use [37].…”
Section: Information Privacy Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, instead of indiscriminately dividing the levels of information sensitivity based on general information types, it is more appropriate to measure information sensitivity by taking users' perception of sensitivity into account. Some scholars define information sensitivity as the perceived intimacy level of information (Lwin, Wirtz, & Williams, 2007). More intimate information is perceived as riskier to disclose because it may lead to potential losses, including psychological (e.g., loss of self-esteem), physical (e.g., loss of health), and material (e.g., loss of property and assets) aspects (Moon, 2000).…”
Section: Information Sensitivitymentioning
confidence: 99%
“…Users of consumer-based strategy may include for-profit firms (e.g., Brasel and Gips 2014;Brocato et al 2015), nonprofits (e.g., Pappu and Cornwell 2014), and governmental bodies (e.g., Burton et al 2015;Lwin et al 2007). Firms may wish to persuade consumers to purchase their products and services; generating consumer insights can help them develop the right products and services for the right prices and effectively persuade consumers to buy them.…”
Section: What Is Consumer-based Strategy?mentioning
confidence: 99%